Eksplorasi Batuan Andesit Berdasarkan Interpretasi Data Resistivitas Di Desa Petangis, Kecamatan Batu Engau, Kabupaten Paser - Sihombing, Jesika; Lepong, Piter; Supriyanto, Supriyanto (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2023)
Exploration activities are very important before mining andesite rocks. This research was conducted in Petangis Village, Batu Engau District, Paser Regency using the Wenner-Schlumberger geoelectric resistivity method with 10 tracks, where 7 tracks have a length of 705 meters in an East-West direction and 3 tracks have a length of 235 meters in a North-South direction. The purpose of this study is to identify the resistivity value of andesite rocks and determine the 2D and 3D distribution of andesite rocks based on the obtained resistivity values. Based on the 2D resistivity section results, it was found that in the study area, andesite rocks have resistivity values ranging from 212-460 Ωm with varying depths of 1-52 meters and the 3D modeling results indicate that andesite rocks are predominantly distributed on the East side with an estimated volume of 1.34588e+007 m3. Keywords: Andesite, Exploration, Resistivity, Wenner-Schlumberger.